2022
DOI: 10.3390/genes13122248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Heat Tolerance at the Flowering Stage Using Chromosome Segment Substitution Lines in Rice

Abstract: High temperature is a major stress in rice production. Although considerable progress has been made in investigating heat tolerance (HT) in rice, the genetic basis of HT at the heading stage remains largely unknown. In this study, a novel set of chromosome segment substitution lines (CSSLs) consisting of 113 lines derived from a heat-resistant indica variety N22 and a heat-sensitive indica variety 9311 was developed and used for the analysis of the genetic basis of HT. The heat sensitivity index (HSI) calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The authors envisioned that the detailed genotypes of TD-CSSL obtained with GBS would enable the identification of chromosome regions associated with traits using a model-based approach [ 35 ]. Therefore, the authors tried to map QTLs using QTL IciMapping software [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors envisioned that the detailed genotypes of TD-CSSL obtained with GBS would enable the identification of chromosome regions associated with traits using a model-based approach [ 35 ]. Therefore, the authors tried to map QTLs using QTL IciMapping software [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that QTL qHTT3.1 was close to qhr3-1 ; while qHTT4.2 and qHTT-X4 were close to qHTB4-2 , which corresponds to previous research and provides validation for these findings [ 17 ]. In addition, qSSR6-1 , qSSR7-1 , qSSR8-1 , qSSR9-1 and qSSR11-1 located on chromosomes 6, 7, 8, 9 and 11 from heat-tolerant indica variety N22 and a heat-sensitive indica variety 9311 [ 32 ]. PS et al used recombinant inbred lines of N22 and IR64 to map heat-tolerant QTL qSTIY5.1 / qSSIY5.2 at the booting stage, which overlapped with previously identified QTLs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A QTL analysis of the genetics underlying HS sensitivity identified a QTL on chromosome 5 in O. rufipogon Griff ( qHTH5 ) coding the HTH5 gene—which affects the pyridoxal phosphate‐binding protein PLPBP—with differential expression patterns in the HS (38 ± 0.5°C from 8:30 am to 3:00 pm) and CS (~30 ± 0.5°C from 3:00 pm to 8:30 am) treatments (Cao et al, 2022). More recently, a genomics study used 113 segment substitution lines derived from heat‐sensitive (9311) and heat‐resistant (N22) indica varieties at the heading stage (38 ± 2°C) (Nguyen et al, 2022). Five QTL associated with HS tolerance were detected based on a seed‐setting rate evaluation: qSSR6‐1 , qSSR7‐1 , qSSR8‐1 , qSSR9‐1 , and qSSR11‐1 located on chromosomes 6, 7, 8, 9, and 11, respectively (Nguyen et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%
“…More recently, a genomics study used 113 segment substitution lines derived from heat‐sensitive (9311) and heat‐resistant (N22) indica varieties at the heading stage (38 ± 2°C) (Nguyen et al, 2022). Five QTL associated with HS tolerance were detected based on a seed‐setting rate evaluation: qSSR6‐1 , qSSR7‐1 , qSSR8‐1 , qSSR9‐1 , and qSSR11‐1 located on chromosomes 6, 7, 8, 9, and 11, respectively (Nguyen et al, 2022).…”
Section: Omics‐driven Breeding For Temperature‐smart Plantsmentioning
confidence: 99%